Cervical Kyphosis in Spinal Muscular Atrophy: A Case Report. Issue 2 (April 2020) - Bernatz, James T.; Anderson, Paul A.; Halanski, Matthew A.
Abstract : Case: A 12-year-old boy with spinal muscular atrophy (SMA) Type II presented 5 years after undergoing spinal growing rod placement with cervical kyphosis at C2-3. He underwent anterior cervical discectomy and fusion but 6 years later developed significant kyphosis at the adjacent C3-4 level. Conclusion: We describe a rare adjacent segment kyphotic condition in a young man with SMA Type II. Clinicians should be cognizant of the risk of cervical kyphosis in adolescent patients with SMA.